2018
DOI: 10.1021/acschembio.8b00360
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Nitric Oxide Responsive Quorum Sensing Circuit in Vibrio cholerae

Abstract: Group behavior of the human pathogen Vibrio cholerae, including biofilm formation and virulence factor secretion, is mediated by a process known as quorum sensing. Quorum sensing is a way by which bacteria coordinate gene expression in response to population density through the production, secretion, and detection of small molecules called autoinducers. Four autoinducer-mediated receptor histidine kinases have been implicated in quorum sensing through the phosphotransfer protein LuxU: CqsS, LuxP/Q, CqsR, and V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 29 publications
4
39
0
Order By: Relevance
“…The study of H‐NOX‐dependent signaling also continues to expand in various directions, including the discovery of another H‐NOX‐like NO sensing protein, NosP (NO signaling protein), by Hossain and Boon . NosPs are FIST domain‐containing proteins found in various bacteria, including several that harbor an H‐NOX .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study of H‐NOX‐dependent signaling also continues to expand in various directions, including the discovery of another H‐NOX‐like NO sensing protein, NosP (NO signaling protein), by Hossain and Boon . NosPs are FIST domain‐containing proteins found in various bacteria, including several that harbor an H‐NOX .…”
Section: Discussionmentioning
confidence: 99%
“…It also inhibits the phosphotransfer from downstream histidine kinase NaHK to phosphotransfer protein HptB and regulates NO‐dependent biofilm formation . NosP from Vibrio cholerae has also been recently demonstrated to contribute to quorum sensing through interaction with a soluble kinase, VpsS . H‐NOX and NosP are both gas‐sensing proteins that are directly involved in biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…86 In our laboratory, we have found that, when ligated to NO, NosP from V. cholerae inhibits the autophosphorylation activity of this quorum sensing histidine kinase, suggesting a potential molecular mechanism by which NO may regulate quorum sensing (and thus biofilm formation) in V. cholera . 92 Interestingly, this would be analogous to the NO and H-NOX/HqsK mediated quorum sensing pathway we discovered in V. harveyi . 54 …”
Section: Nitric Oxide and Nosp Signaling In Bacterial Biofilmsmentioning
confidence: 74%